Temporary fixing composition, temporary fixing adhesive, and method for producing thin wafer

By controlling the equivalent of the aromatic ring bonding to heteroatoms, using a specific composition to peel off the substrate under low power laser, the problems of peeling difficulties and temperature rise in the prior art are solved, and the substrate peeling effect with high efficiency and low heat influence is achieved.

JP7628657B2Active Publication Date: 2025-02-10DENKA CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024541004
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2023-01-31
Filing Date
2024-01-22
Publication Date
2025-02-10
Estimated Expiration
2044-01-22

AI Technical Summary

Technical Problem

In the prior art, temporary fixatives are difficult to effectively peel off under low-power laser irradiation, and high-power laser irradiation is likely to cause the substrate temperature to rise, affecting the substrate quality.

Method used

By controlling the equivalent amount of aromatic rings bound to heteroatoms in the temporary fixation composition, the temporary fixation composition formed by using polymer compounds containing aromatic rings, photoradical polymerization initiators and ultraviolet absorbers with polymerizable functional groups can be effectively peeled off under low-power lasers and achieve rapid curing through photoradical polymerization.

Benefits of technology

It is possible to effectively peel off the substrate under low-power laser irradiation, while suppressing the rise in substrate temperature, ensuring the quality of the substrate, and reducing gas generation during the peeling process, improving cleaning performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007628657000001
    Figure 0007628657000001
  • Figure 0007628657000002
    Figure 0007628657000002
  • Figure 0007628657000003
    Figure 0007628657000003
Patent Text Reader

Abstract

A composition for temporary fixing, said composition comprising: (A) a polymerizable component including a (meth)acrylate that contains an aromatic ring which is bonded to a heteroatom; (B) a photoradical polymerization initiator; and (C) an ultraviolet absorber having a polymerizable functional group, wherein in 1 g of the composition for temporary fixing, the equivalent amount of the aromatic ring which is bonded to the heteroatom is 0.50-3 mmol.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a temporary fixing composition, a temporary fixing adhesive, and a method for producing a thin wafer. [Background technology]

[0002] In the manufacture of electronic devices, inorganic materials such as silicon are often used as substrates, and wafer-type substrates with a thickness of about several hundred microns are often used, which are obtained by forming an insulating film on the surface, forming circuits, and thinning by grinding. However, since many substrates are made of brittle and easily cracked materials, measures to prevent damage are necessary, especially when thinning by grinding. A conventional method for this measure is to apply a temporary protective tape to the surface opposite to the surface to be ground (also called the back surface), which can be peeled off after the processing process is completed. This tape uses an organic resin film as the base material, and while it is flexible, it is insufficient in strength and heat resistance, making it unsuitable for use in high-temperature processes.

[0003] In response to this, a system has been proposed in which an electronic device substrate is bonded to a support member such as silicon or glass via an adhesive, thereby providing sufficient durability to withstand the conditions of the back grinding and back electrode formation processes. In this case, the adhesive layer used to bond the substrate to the support member is important. This must be able to bond the substrate to the support member without any gaps, and must be durable enough to withstand subsequent processes. Finally, it must be possible to easily peel off the thinned wafer from the support member, i.e., to temporarily fix it.

[0004] The processing of such wafers mainly involves a spin coating step, a vacuum bonding and light curing step, a thinning step by grinding and polishing, a high-temperature treatment step, a laser peeling step, and a temporary fixing agent removal step.

[0005] In the spin coating process, in order to form a uniform film of the temporary fixative on the wafer, it is required that the temporary fixative has an appropriate viscosity and is a Newtonian fluid (or has a shear viscosity that is independent of the shear rate).

[0006] In the vacuum bonding / UV curing process, the temporary fixative must be able to cure in a short time by irradiating it with ultraviolet (UV) light or other light on a supporting member such as glass, and must generate little outgassing (low outgassing properties).

[0007] In the thinning process by grinding and polishing, in order to avoid damage caused by the load of the grinding machine being applied locally to the substrate, the temporary fixative must have an appropriate hardness to distribute the load in the in-plane direction while preventing localized sinking of the substrate and maintaining flatness. In addition, it must also have adhesion to the support member, an appropriate elastic modulus to protect the edges, and chemical resistance.

[0008] In the high-temperature treatment process, the temporary fixing agent is required to have heat resistance capable of withstanding high-temperature treatment in a vacuum for a long period of time (for example, at 300° C. or higher for one hour or more).

[0009] In the laser peeling process, the temporary fixative is required to be able to be peeled off quickly by a laser such as a UV laser.

[0010] In the removal step, in addition to easy removability so that the substrate can be easily peeled off from the support member, the adhesive is required to have cohesive properties so that no adhesive residue remains on the substrate after peeling, and easy cleanability.

[0011] In view of this background, for example, Patent Document 1 discloses a temporary fixing composition containing (A-1) a monofunctional (meth)acrylate whose side chain is an alkyl group having 18 or more carbon atoms and whose homopolymer has a Tg of -100°C to 60°C, (A-2) a polyfunctional (meth)acrylate, (B) a polyisobutene homopolymer and / or a polyisobutene copolymer, and (C) a photoradical polymerization initiator, and claims that the composition has excellent heat resistance, low outgassing properties, and peelability. [Prior art documents] [Patent documents]

[0012] [Patent Document 1] International Publication No. 2021 / 235406 Summary of the Invention [Problem to be solved by the invention]

[0013] To peel off the hardened temporary fixing agent (i.e., adhesive layer) on the wafer, a laser is swept through a transparent support member such as glass to decompose the adhesive layer at the irradiated location, forming a hole (a recess that is covered with the support member). The gas vaporized in the hole expands at high temperature, pushing up the support member, making it easier to peel off.

[0014] However, when a laser is irradiated, the radiant energy is absorbed, and the irradiated area generates heat and the temperature rises. Therefore, the higher the output of the laser irradiation, the easier it is to decompose the hardened temporary fixing agent, but the temperature of the substrate adjacent to the temporary fixing agent also rises, which is not preferable from the viewpoint of ensuring the quality of the substrate.

[0015] The present invention has been completed in view of the above problems, and an object of the present invention is to provide, in one embodiment, a temporary fixing composition that has excellent peelability even when irradiated with a low-power laser. In another embodiment, the present invention is to provide a temporary fixing adhesive that includes such a temporary fixing composition, and a method for manufacturing a thin wafer using the temporary fixing adhesive. [Means for solving the problem]

[0016] As a result of intensive research, the present inventors have found that the above-mentioned problems can be solved by controlling the equivalent weight of the aromatic ring bonded to the heteroatom in the temporary fixing composition. The details of the reason will be described later, but it is presumed that the aromatic ring bonded to the heteroatom is likely to absorb a laser of a specific wavelength, and the adhesive layer can be decomposed even with low energy. The present invention has been completed based on the above findings, and is exemplified below.

[0017] [1] A temporary fixing composition comprising the following (A) to (C): (A) a polymerizable component comprising a (meth)acrylate containing an aromatic ring bonded to a heteroatom. (B) Photoradical polymerization initiator (C) UV absorber having a polymerizable functional group The temporary fixing composition, wherein the equivalent of an aromatic ring bonded to a heteroatom contained in 1 g of the temporary fixing composition is 0.50 mmol or more and 3 mmol or less. [2] The component (A) is 9,9-bis[4-(2-hydroxyphenyl)- 1 ~C 20 Alkoxy)phenyl]fluorendi(meth)acrylate, C 1 ~C 20 Alkoxylated bisphenol A di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy) 1 ~C 20 The temporary fixing composition according to [1], comprising one or more selected from the group consisting of a 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, or a structural isomer thereof. [3] The temporary fixing composition according to [1], wherein the component (A) contains one or more selected from the group consisting of nonylphenoxy polyethylene glycol (meth)acrylate, phenoxyethyl (meth)acrylate, or structural isomers thereof. [4] The temporary fixing composition according to any one of [1] to [3], wherein the component (B) is one or more selected from bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime). [5] The temporary fixing composition according to any one of [1] to [4], wherein the component (C) has one or more skeletons selected from the group consisting of a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, and a phenol skeleton, and has a polymerizable functional group. [6] The temporary fixing composition according to any one of [1] to [5], containing 0.01 to 5 parts by mass of the (B) component and 0.005 to 15 parts by mass of the (C) component relative to a total of 100 parts by mass of the (A) component. [7] A temporary fixing adhesive comprising the temporary fixing composition according to any one of [1] to [6]. [8] A method for producing a thin wafer using the temporary fixing adhesive according to [7], a step of bonding a base material of a thin wafer and an optically transparent support member via the temporary fixing adhesive; a step of photocuring the temporary fixing adhesive from the support member side to form an adhesive layer and bonding the base material and the support member; processing the substrate to form a thin wafer; a step of irradiating the support member with light having a wavelength of 350 nm to 385 nm to decompose the adhesive layer and peel off the thin wafer from the support member; The method includes: [9] A composition comprising the following (A) to (C): (A) a polymerizable component comprising a (meth)acrylate containing an aromatic ring bonded to a heteroatom. (B) Polymerization initiator (C) UV absorber having a polymerizable functional group A composition, wherein the equivalent amount of aromatic rings bonded to heteroatoms contained in 1g of said composition is 0.50 mmol or more and 3 mmol or less. Effect of the Invention

[0018] According to one embodiment of the present invention, it is possible to provide a temporary fixing composition having excellent peelability even when irradiated with a low-power laser. In another embodiment, the present invention can provide a temporary fixing adhesive containing such a temporary fixing composition, and a method for producing a thin wafer using the temporary fixing adhesive. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] Next, the embodiments of the present invention will be described in detail. It should be understood that the present invention is not limited to the following embodiments, and that appropriate design changes, improvements, etc. may be made based on the ordinary knowledge of those skilled in the art without departing from the spirit of the present invention.

[0020] In this specification, unless otherwise specified, a numerical range includes its upper and lower limits. In this specification, (meth)acrylate refers to a compound having one or more (meth)acryloyl groups in one molecule. Monofunctional (meth)acrylate refers to a compound having one (meth)acryloyl group in one molecule. Multifunctional (meth)acrylate refers to a compound having two or more (meth)acryloyl groups in one molecule. n-functional (meth)acrylate refers to a compound having n (meth)acryloyl groups in one molecule. The polymerizable functional group in the multifunctional (meth)acrylate may have only acryloyl groups, may have only methacryloyl groups, or may have both acryloyl and methacryloyl groups. In addition, "C 1 ~C 20 " or "C 10 ~C 20 " means a hydrocarbon group having 1 to 20 carbon atoms or a hydrocarbon group having 10 to 20 carbon atoms.

[0021] In one embodiment, the present invention provides a temporary fixing composition containing the following (A) to (C): (A) a polymerizable component comprising a (meth)acrylate containing an aromatic ring bonded to a heteroatom. (B) Photoradical polymerization initiator (C) UV absorber having a polymerizable functional group Here, the equivalent amount of the aromatic ring bonded to the heteroatom contained in 1 g of the temporary fixing composition is 0.5 mmol or more and 3.0 mmol or less.

[0022] (1. Component (A)) The polymerizable component (A) contained in the temporary fixing composition of this embodiment plays a role in forming a (meth)acrylic polymer skeleton. The temporary fixing composition of this embodiment may also contain a non-polymerizable component, but the amount of the non-polymerizable component is preferably less than 15 parts by mass per 100 parts by mass of the total of the non-polymerizable component and the (A) component. In this specification, the term "non-polymerizable component" is defined as anything other than the (B) component, i.e., anything not used in the technical field as a photoradical polymerization initiator.

[0023] The polymerizable component (A) contained in the temporary fixing composition of the present embodiment contains a (meth)acryloyl group and plays a role in forming a (meth)acrylic polymer skeleton. The polymerizable component is preferably a polymerizable organic compound component. The (A) component may preferably contain a compound having two or more (meth)acryloyl groups. The (A) component may be a monofunctional (meth)acrylate, a bifunctional (meth)acrylate, or a trifunctional or higher polyfunctional (meth)acrylate, or a mixture thereof. The (A) component may also preferably contain a combination of a polyfunctional (meth)acrylate and a monofunctional (meth)acrylate (more preferably a combination of a bifunctional (meth)acrylate and a monofunctional (meth)acrylate).

[0024] The polyfunctional (meth)acrylate that the (A) component may contain may be an aromatic bifunctional (meth)acrylate, an alicyclic bifunctional (meth)acrylate, or a mixture thereof, from the viewpoint of providing a rigid structure. The (A) component may contain an acyclic polyfunctional (meth)acrylate. The polyfunctional (meth)acrylate may be a monomer or a polymer, or may be a mixture thereof. That is, the above-mentioned polymerizable polymer may be a polymer of a polyfunctional (meth)acrylate. The molecular weight of the polyfunctional (meth)acrylate monomer is preferably 900 or less, more preferably 700 or less, even more preferably 500 or less, and even more preferably 400 or less.

[0025] The weight average molecular weight of the multifunctional (meth)acrylate polymer is preferably 5000 to 200000. When the weight average molecular weight of the multifunctional (meth)acrylate polymer is 5000 or more, a suitable viscosity can be obtained when blended with other polymerizable components. When the weight average molecular weight of the multifunctional (meth)acrylate polymer is 10000 or more, a suitable thickening effect can be obtained. From this viewpoint, the weight average molecular weight of the multifunctional (meth)acrylate polymer is more preferably 6000 or more, and even more preferably 7000 or more. When the weight average molecular weight of the multifunctional (meth)acrylate polymer is 200000 or less, good spin coatability with low shear rate dependency can be obtained. From this viewpoint, the weight average molecular weight of the multifunctional (meth)acrylate polymer is more preferably 190000 or less, even more preferably 180000 or less, even more preferably 150000 or less, and particularly preferably 100000 or less.

[0026] The functional group equivalent weight of the polyfunctional (meth)acrylate polymer is preferably from 500 to 20,000, more preferably from 700 to 10,000, and most preferably from 1,000 to 7,000.

[0027] Examples of aromatic bifunctional (meth)acrylates include 9,9-bis[4-(2-hydroxyphenyl)-2-(2-methylphenyl)-1,2-diphenyl-2-propanediol (meth)acrylate. 1 ~C 20 Alkoxy)phenyl]fluorendi(meth)acrylate, C 1 ~C 20 Alkoxylated bisphenol A di(meth)acrylate, benzyl di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy)C 1 ~C 20 Examples of the di(meth)acrylate include 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, and structural isomers thereof. Preferably, the di(meth)acrylate may include a di(meth)acrylate having a condensed ring skeleton, such as a skeleton of fluorene, indene, indecene, anthracene, azulene, or triphenylene.

[0028] Examples of alicyclic bifunctional (meth)acrylates include C 1 ~C 20 Alkoxylated hydrogenated bisphenol A di(meth)acrylate, 1,3-di(meth)acryloyloxyadamantane, tricyclo C 10 ~C 20 Alkanedimethanol di(meth)acrylate, Dicyclo C 5 ~C 20 di(meth)acrylate, or a structural isomer thereof.

[0029] Examples of the acyclic bifunctional (meth)acrylate include 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, 1,10-decanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, neopentyl glycol modified trimethylolpropane di(meth)acrylate, stearic acid modified pentaerythritol di(meth)acrylate, tripropylene glycol di(meth)acrylate, and caprolactone modified hydroxypivalic acid neopentyl glycol di(meth)acrylate.

[0030] The component (A) may also contain a polyfunctional (meth)acrylate having three or more functional groups. Examples of the trifunctional (meth)acrylate include isocyanuric acid ethylene oxide modified tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, and tris[(meth)acryloyloxyethyl]isocyanurate.

[0031] Examples of tetrafunctional or higher (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate.

[0032] Furthermore, the monofunctional (meth)acrylate that may be contained in the component (A) is preferably a monofunctional (meth)acrylate having a molecular weight of 550 or less, and more preferably a monofunctional alkyl (meth)acrylate having an alkyl group.

[0033] The alkyl group is preferably one or more selected from linear alkyl groups, branched alkyl groups, and alicyclic alkyl groups, and more preferably one or more selected from linear alkyl groups and branched alkyl groups. From the viewpoint of improving compatibility with other components, it is preferable that the (A) component has a long chain and branched or cyclic alkyl group, for example, a branched alkyl group having 18 to 40 carbon atoms, more preferably 18 to 32 carbon atoms, such as an isostearyl group, an isotetracosanyl group (e.g., 2-decyl-1-tetradecanyl group), an isotriacontanyl group (e.g., 2-tetradecyl-1-octadecanyl group), or a cycloalkyl group. By using such a component having a long chain, high molecular weight, and strong aliphatic hydrocarbon properties (more preferably by increasing the aliphatic hydrocarbon properties of the entire system), it is possible to improve the low volatility, chemical resistance, and heat resistance required for the temporary fixing composition.

[0034] As the (A) component, one or more selected from the group consisting of stearyl (meth)acrylate, isostearyl (meth)acrylate, behenyl (meth)acrylate, 2-decyl-1-tetradecanyl (meth)acrylate, 2-dodecyl-1-hexadecanyl (meth)acrylate, and 2-tetradecyl-1-octadecanyl (meth)acrylate are preferred. As the (A) component, the (meth)acrylate of the following formula 1 is preferred.

[0035] [ka] In the formula, R 1 R is a hydrogen atom or a methyl group, and a hydrogen atom is more preferable. 2 is an alkyl group having a carbon number of preferably 18 to 32. One or more of these (meth)acrylates can be used.

[0036] R 2 As the monofunctional alkyl (meth)acrylate in which is an alkyl group having 18 to 32 carbon atoms, preferred are (meth)acrylates having a linear or branched alkyl group, such as stearyl (meth)acrylate, isostearyl (meth)acrylate, nonadecyl (meth)acrylate, eicodecyl (meth)acrylate, behenyl (meth)acrylate, 2-decyl-1-tetradecanyl (meth)acrylate, and 2-tetradecyl-1-octadecanyl (meth)acrylate.

[0037] In the temporary fixing composition of this embodiment, the component (A) contains a (meth)acrylate that contains an aromatic ring bonded to a heteroatom.

[0038] The (meth)acrylate containing an aromatic ring bonded to a heteroatom may be a monofunctional (meth)acrylate, a bifunctional (meth)acrylate, a trifunctional or higher polyfunctional (meth)acrylate, or a mixture thereof. Preferably, the (A) component may include a combination of a polyfunctional (meth)acrylate and a monofunctional (meth)acrylate, a combination of a polyfunctional (meth)acrylate and a polymerizable polymer, or a combination of a polyfunctional (meth)acrylate, a monofunctional (meth)acrylate, and a polymerizable polymer.

[0039] In the (meth)acrylate containing an aromatic ring bonded to a heteroatom, the number of aromatic rings per molecule is not particularly limited, and may be 1, 2, 3, 4 or more, or a mixture of (meth)acrylates having aromatic rings of these numbers. In addition, in the (meth)acrylate containing an aromatic ring bonded to a heteroatom, an aromatic ring that is not bonded to a heteroatom may be present.

[0040] As described later, the (meth)acrylate containing an aromatic ring bonded to a heteroatom constitutes a part or all of the equivalent amount of the aromatic ring bonded to a heteroatom contained in 1 g of the temporary fixing composition of the present invention.

[0041] As the (meth)acrylate containing an aromatic ring bonded to a hetero atom, examples of the bifunctional (meth)acrylate include 9,9-bis[4-(2-hydroxyphenyl)-2,4-diphenyl-2,4-diphenyl-1,2 ... 1 ~C 20 Alkoxy)phenyl]fluorendi(meth)acrylate, C 1 ~C 20 Alkoxylated bisphenol A di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy) 1 ~C 20 Examples of the di(meth)acrylate include one or more selected from the group consisting of bisphenol A di(meth)acrylate, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane (including ethoxylated bisphenol A di(meth)acrylate), and structural isomers thereof. Preferably, the di(meth)acrylate may include a di(meth)acrylate having a condensed ring skeleton, such as a skeleton of fluorene, indene, indecene, anthracene, azulene, or triphenylene.

[0042] Examples of monofunctional (meth)acrylates containing an aromatic ring bonded to a heteroatom include nonylphenoxy polyethylene glycol (meth)acrylate (including nonylphenol EO-modified (meth)acrylate), phenoxyethyl (meth)acrylate, and at least one selected from the group consisting of structural isomers thereof.Preferably, (meth)acrylates having a condensed ring skeleton, such as a skeleton of fluorene, indene, indecene, anthracene, azulene, or triphenylene may be included.

[0043] In a preferred embodiment, the total amount of (meth)acrylates containing an aromatic ring bonded to a heteroatom in the (A) component may be in the range of 5 to 100% by mass relative to the total mass of the (A) component. Specifically, the total amount of (meth)acrylates containing an aromatic ring bonded to a heteroatom in the (A) component may be preferably 5% by mass or more, 10% by mass or more, 15% by mass or more, 20% by mass or more, 25% by mass or more, 30% by mass or more, 40% by mass or more, 50% by mass or more, or 60% by mass or more relative to the total mass of the (A) component. In addition, the total amount of (meth)acrylates containing an aromatic ring bonded to a heteroatom in the (A) component may be preferably 100% by mass or less, 90% by mass or less, 85% by mass or less, 80% by mass or less, 75% by mass or less, or 70% by mass or less.

[0044] The content of the component (A) is preferably 60 to 100 mass %, 70 to 98 mass %, 80 to 96 mass %, or 85 to 94 mass %, based on the total amount of the temporary fixing composition.

[0045] In a preferred embodiment, the amount of the non-polymerizable component contained in the temporary fixing composition of the present embodiment may be 0% by mass or more and less than 10% by mass, or 0% by mass or more and less than 5% by mass. The amount of the non-polymerizable component may be 10% by mass or less, or 5% by mass or less. More preferably, the temporary fixing composition of the present embodiment may not contain a non-polymerizable component except for the component (B).

[0046] (2.(B) component) The polymerization initiator, which is the component (B) contained in the temporary fixing composition of the present embodiment, and preferably a photoradical polymerization initiator, is a substance that can initiate polymerization of the component (A) upon irradiation with light. The photoradical polymerization initiator is, for example, a compound whose molecules are cleaved and split into two or more radicals upon irradiation with ultraviolet light or visible light (e.g., wavelength 350 to 700 nm, preferably 365 to 500 nm, more preferably 385 to 450 nm). Examples of photoradical polymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)-butan-1-one, 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime). The component (B) may contain one or more of these, or a combination of two or more of them.

[0047] In a preferred embodiment of the present invention, the component (B) contained in the temporary fixing composition may contain an acylphosphine oxide-based compound. Examples of preferred acylphosphine oxide-based compounds include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide. As the photoradical polymerization initiator, it is preferable that it is highly sensitive, has excellent deep curing properties due to its photofading properties, and has an absorption wavelength range for generating radicals that extends to a relatively long wavelength range. In the above-mentioned preferred compounds, the absorption wavelength range is in the range up to a wavelength of about 440 nm, which is significantly different from the absorption wavelength range of the UV absorber used in the UV laser peeling process described later. In other words, the degree of UV curing inhibition by the UV absorber is small, and radical polymerization can be initiated with light of a longer wavelength. Therefore, even in the coexistence of a UV absorber, the effect of initiating radical polymerization and curing efficiently at a relatively high speed can be obtained.

[0048] In a preferred embodiment, the photoradical polymerization initiator can be selected based on absorbance. Specifically, the photoradical polymerization initiator can be selected from one or more compounds that satisfy one or more of the following conditions when dissolved at a concentration of 0.1 mass % in a solvent (e.g., acetonitrile, toluene, etc.) that does not have a maximum absorption in the wavelength region of 300 to 500 nm: absorbance of 0.5 or more at a wavelength of 365 nm, absorbance of 0.5 or more at a wavelength of 385 nm, and absorbance of 0.5 or more at a wavelength of 405 nm. Examples of compounds that satisfy such conditions include 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime), which has an absorbance of 0.5 or more at a wavelength of 365 nm when dissolved in acetonitrile as a solvent at a concentration of 0.1% by mass; 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, which has an absorbance of 0.5 or more at wavelengths of 365 nm and 385 nm; and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 2,4,6-trimethylbenzoyldiphenylphosphine oxide, which have an absorbance of 0.5 or more at wavelengths of 365 nm, 385 nm, and 405 nm.

[0049] In addition, from the viewpoint of achieving both the curing property by the photoradical polymerization initiator and the UV laser peeling, bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium, which has an absorption wavelength range of 400 to 500 nm, can also be used as the photoradical polymerization initiator.

[0050] As the (B) photoradical polymerization initiator, one or more selected from acylphosphine oxide compounds, titanocene compounds, and α-aminoalkylphenone compounds are preferred in terms of reaction speed, heat resistance after curing, low outgassing, and absorption characteristics in a region different from the wavelength of the UV laser used in the UV laser peeling described later and the absorption wavelength region of the UV absorber used in the UV laser peeling. In addition to the above, oxime ester compounds can also be selected as photoradical polymerization initiators for resin compositions for temporary fixing applications for preventing damage from bonding of the substrate to be processed to the support member to the heating step, which is not a layer for responding to the UV laser peeling step, among the temporary fixing compositions having the structure described later.

[0051] Examples of the acylphosphine oxide compound include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, etc. Among these, bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide is particularly preferred.

[0052] The titanocene compound may be bis(η5-2,4-cyclopentadien-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium.

[0053] Examples of the α-aminoalkylphenone compounds include 2-benzyl-2-dimethylamino-1-(4-morpholinophenyl)-butan-1-one, 2-dimethylamino-2-(4-methylbenzyl)-1-(4-morpholin-4-ylphenyl)-butan-1-one, and the like.

[0054] Examples of oxime ester compounds include 1-[4-(phenylthio)phenyl]-1,2-octanedione 2-O-benzoyloxime, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime), etc. Among these, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime) is preferred.

[0055] In a preferred embodiment of the present invention, the component (B) in the temporary fixing composition is one or more selected from bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime).

[0056] The amount of the photoradical polymerization initiator (B) used is preferably 0.01 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, even more preferably 0.1 to 2 parts by mass, and even more preferably 0.1 to 1 part by mass, relative to 100 parts by mass of the total of the components (A) in terms of reaction rate, heat resistance after curing, and low outgassing. When the amount of the component (B) is 0.01 part by mass or more, sufficient curability is obtained, and when it is 5 parts by mass or less, the effect of low outgassing and heat resistance being less likely to be impaired is obtained.

[0057] (3.(C) component) The ultraviolet absorber (UV absorber) having a polymerizable functional group, which is the component (C) contained in the temporary fixing composition of this embodiment, refers to a compound whose molecules are cut and decomposed / vaporized by irradiation with ultraviolet or visible light laser, and the decomposition / vaporization occurs at the interface between the support member and the cured product of the temporary fixing composition (hereinafter also referred to as the temporary fixing agent), causing the loss of adhesion between the cured product of the temporary fixing composition and the support member that was maintained until just before the UV laser peeling process. The component (C) is a compound having one or more skeletons selected from the group consisting of a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, and a phenol skeleton (preferably a hindered phenol skeleton). The reason for having these skeletons is to obtain the degree of overlap with the UV laser light wavelength in the UV absorption wavelength region, UV absorption characteristics at the same wavelength, low outgassing properties, and heat resistance. The polymerizable functional group of the component (C) is preferably a (meth)acryloyl group. In order to obtain the effects of the present invention well, the component (C) preferably has an absorption peak for light having a wavelength of 350 nm to 385 nm.

[0058] Examples of the component (C) include one or more members selected from the group consisting of 2-[2-hydroxy-5-[2-((meth)acryloyloxy)ethyl]phenyl]-2H-benzotriazole, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl (meth)acrylate, 2-(2-(meth)acryloyloxy,5-methyl)phenyl-2H-benzotriazole, 1,1-bis-[2-(meth)acryloyloxy,3-(2H-benzotriazol-2-yl),5-tertiaryoctyl]methane, and 2,2'-dihydroxy-4,4'-di(meth)acryloyloxybenzophenone, which are particularly preferred in terms of compatibility with the resin component, UV absorption characteristics, low outgassing, and heat resistance.

[0059] The amount of component (C) is preferably 0.005 to 15 parts by mass, more preferably 0.01 to 12 parts by mass, more preferably 0.1 to 10 parts by mass, and even more preferably 0.5 to 7 parts by mass, relative to 100 parts by mass of the total of components (A). When the amount is 0.01 part by mass or more, a sufficient UV laser peeling speed is obtained, and when the amount is 15 parts by mass or less, the effect of low outgassing properties and heat resistance being less likely to be impaired is obtained.

[0060] (4. Temporary Fixing Composition) The temporary fixing composition of the present invention has an equivalent amount of aromatic rings bonded to heteroatoms of 0.50 mmol or more and 3 mmol or less per 1 g.

[0061] Generally, the absorption peak of an aromatic ring is at about 200 nm, but when the element adjacent to the aromatic ring is a hetero element such as P, S, or O, the conjugation length is extended and the absorption edge is extended to 355 nm. This is presumably because it is more likely to absorb the energy of the laser light and to be decomposed. However, the present invention is not bound by any theory.

[0062] From the above viewpoints, in order to enhance the absorption of the energy of the laser beam, the equivalent of the aromatic ring bonded to the heteroatom contained in the temporary fixing composition 1g is set to 0.50 mmol or more. The equivalent of the aromatic ring bonded to the heteroatom contained in the temporary fixing composition 1g is preferably 0.55 mmol or more, more preferably 0.6 mmol or more, more preferably 0.60 mmol or more, even more preferably 0.65 mmol or more, even more preferably 0.7 mmol or more, and even more preferably 0.70 mmol or more.

[0063] However, if the equivalent of the aromatic ring bonded to the heteroatom is too high, it may be damaged when heat-treated because it cannot follow the distortion caused by the difference in linear expansion coefficient between the support member and the wafer. From this viewpoint, the equivalent of the aromatic ring bonded to the heteroatom contained in 1g of the temporary fixing composition is set to 3mmol or less. The equivalent of the aromatic ring bonded to the heteroatom contained in 1g of the temporary fixing composition is preferably 3.0mmol or less, preferably 2.8mmol or less, more preferably 2.5mmol or less, even more preferably 2mmol or less, even more preferably 2.0mmol or less, even more preferably 1.9mmol or less, even more preferably 1.8mmol or less, even more preferably 1.7mmol or less, and even more preferably 1.6mmol or less.

[0064] The equivalent of the aromatic ring bonded to the heteroatom does not necessarily have to come from component (A), but may come from component (B) or component (C).

[0065] If the equivalent of aromatic rings bonded to heteroatoms contained in 1 g of the temporary fixing composition is 0.50 mmol or more and 3 mmol or less, the adhesive layer can be decomposed even with a low laser output, so that peeling can be performed with reduced heat generation. In addition, since the decomposition of the adhesive layer is promoted, when the remaining adhesive layer is washed after peeling, the advantage that it is easy to wash can be expected.

[0066] (5. Temporary Fixing Adhesive) The temporary fixing composition of the present invention can be used as a temporary fixing adhesive, particularly as a temporary fixing adhesive for the production of electronic devices such as thin wafers, etc. The temporary fixing adhesive preferably consists solely of the temporary fixing composition of the present invention.

[0067] (6. Thin Wafer Manufacturing Method) In another embodiment of the present invention, a method for manufacturing a thin wafer using the temporary fixing adhesive of the present invention is also provided. The method includes a step of bonding a base material of a thin wafer and an optically transparent support member via the temporary fixing adhesive, a step of photocuring the temporary fixing adhesive from the support member side to form an adhesive layer and bonding the base material and the support member, a step of processing the base material to form a thin wafer, and a step of irradiating light having a wavelength of 350 nm to 385 nm from the support member side to decompose the adhesive layer and peeling the thin wafer from the support member.

[0068] The method for bonding the thin wafer substrate and the optically transparent support member is not particularly limited, but is typically performed by applying a temporary fixing adhesive to the optically transparent support member and then bonding the substrate to the surface on which the temporary fixing adhesive has been applied.

[0069] The temporary fixing adhesive can be applied by known application methods such as spin coating, screen printing, and various coaters. The viscosity of the temporary fixing composition of the present embodiment is preferably 500 mPa·s or more, more preferably 1000 mPa·s or more, at 23°C (atmospheric pressure), in terms of applicability and workability. The viscosity of the temporary fixing composition of the present embodiment is preferably 15000 mPa·s or less, more preferably 10000 mPa·s or less, and even more preferably 5000 mPa·s or less, at 23°C (atmospheric pressure), in terms of applicability and workability. When the viscosity is 500 mPa·s or more, the composition has excellent applicability, particularly applicability by spin coating. When the viscosity is 15000 mPa·s or less, the composition has excellent workability. The viscosity can be measured by a known viscometer.

[0070] Spin coating is a method for applying the composition to the surface of a support member by, for example, dropping a liquid composition onto the support member and rotating the support member at a predetermined rotation speed. By spin coating, a high-quality coating film can be efficiently produced.

[0071] When bonding the substrate to be processed and the support member, the bonding agent is irradiated with light to cure the bond. The wavelength of the light can be appropriately selected depending on the type of the photoradical polymerization initiator (B), and is typically 350 nm to 700 nm. In particular, the amount of energy of the bond is preferably 1 to 20,000 mJ / cm for visible light or ultraviolet light (wavelength or central wavelength 365 to 405 nm). 2 It is preferable to irradiate so that the energy amount is 1 mJ / cm 2 Above this level, sufficient adhesion is obtained, and 20,000 mJ / cm 2 If the energy level is less than this, the productivity is excellent, decomposition products from the photoradical polymerization initiator are unlikely to be generated, and outgassing is suppressed. In terms of productivity, adhesion, low outgassing, and easy peeling, it is 1000 to 10000 mJ / cm 2 It is preferable that the wavelength of the light used here is selected to be in a range different from the wavelength of the laser light used to decompose the adhesive layer, which will be described later.

[0072] Although there is no particular restriction on the substrate to be processed and the support member, it is preferable that at least one of the substrates is a transparent substrate that transmits light. Examples of the transparent substrate include inorganic substrates such as crystal, glass, quartz, calcium fluoride, magnesium fluoride, and organic substrates such as plastic. Among these, inorganic substrates are preferable because they are versatile and can provide a large effect. Among the inorganic substrates, one or more selected from glass and quartz are preferable.

[0073] After bonding the substrate to the support member, the substrate is processed to form a thin wafer, typically by thinning through grinding and polishing, and high-temperature treatment.

[0074] After forming the thin wafer, the adhesive layer is decomposed by irradiating it with light having a wavelength of 350 nm to 385 nm from the support member side. For example, the adhesive layer can be decomposed by irradiating it with a UV laser having a wavelength of 350 nm to 385 nm so as to scan the entire surface. As described above, aromatic rings bonded to heteroatoms tend to absorb the energy of laser light having a wavelength of around 355 nm, so by setting the wavelength of the laser light within the range of 350 nm to 385 nm, the effect of improving energy absorption becomes more significant. EXAMPLES

[0075] The present invention will be described in more detail below based on examples and comparative examples, but the present invention is not limited to these.

[0076] Unless otherwise specified, the experiments were carried out at 23°C and humidity of 50%. Temporary fixing compositions having the compositions (units: parts by mass) shown in the table below were prepared and evaluated. The following compounds were selected as each component.

[0077] (composition) The following was used as component (A): APB-001 (multifunctional acrylate polymer, Negami Chemical Industries "APB-001", weight average molecular weight 72,000, functional group equivalent weight 1400) A-BPEF-2: 9,9-bis[4-(2-hydroxyethoxy)phenyl]fluorene diacrylate ("NK Ester A-BPEF-2" manufactured by Shin-Nakamura Chemical Co., Ltd.) ABE-300: Ethoxylated bisphenol A diacrylate ("NK Ester ABE-300" manufactured by Shin-Nakamura Chemical Co., Ltd., in the following structural formula: R = -CH 2 CH 2 O-, m+n≒3) A-BPE-2: Ethoxylated bisphenol A diacrylate ("NK Ester A-BPE-2" manufactured by Shin-Nakamura Chemical Co., Ltd., in the following structural formula: R = -CH 2 CH 2 O-, m=n=1) [ka] HBPE-4: EO modified hydrogenated bisphenol A diacrylate ("HBPE-4" manufactured by Daiichi Kogyo Seiyaku Co., Ltd., m+n≒4) A-DOD-N: 1,10-decanediol diacrylate ("A-DOD-N" manufactured by Shin-Nakamura Chemical Co., Ltd.) HX-220: Caprolactone-modified hydroxypivalic acid neopentyl glycol diacrylate ("Kayarad HX-220" manufactured by Nippon Kayaku Co., Ltd., m+n≒2) HX-620: Caprolactone-modified hydroxypivalic acid neopentyl glycol diacrylate ("Kayarad HX-620" manufactured by Nippon Kayaku Co., Ltd., m+n≒4) A-TMPT: Trimethylolpropane triacrylate ("A-TMPT" manufactured by Shin-Nakamura Chemical Co., Ltd.) RC110C (Both-terminated acrylate polymer, Kaneka Corporation "XMAP RC110C", weight average molecular weight 12,000, functional group equivalent 6,000) M-113: Nonylphenol EO modified acrylate ("Aronix M-113" manufactured by Toagosei Co., Ltd., n ≒ 4) ISTA: Isostearyl acrylate ("ISTA" manufactured by Osaka Organic Chemical Industry Co., Ltd.)

[0078] Bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide (BASF "Irgacure 819") was used as component (B).

[0079] The following was used as component (C): RUVA-93: 2-[2-hydroxy-5-[2-(methacryloyloxy)ethyl]phenyl]-2H-benzotriazole (Otsuka Chemical Co., Ltd. "RUVA-93") P-66: 2,2'-dihydroxy-4,4'-diacryloyloxybenzophenone (Daiwa Chemical Industry Co., Ltd. "DAINSORB P-66")

[0080] (Liquid sample preparation) As shown in Tables 1-1 and 1-2, for each of the comparative examples and examples, the materials were heated and mixed at 60°C to obtain a uniform liquid composition for temporary fixing. In addition, Tables 1-1 and 1-2 show the presence or absence of an aromatic ring bonded to a heteroatom for each component, and the equivalent of the aromatic ring bonded to a heteroatom calculated from the amount of each component in each example is shown in parentheses. The calculation formula is as follows. Equivalent weight of aromatic rings bonded to heteroatoms (mmol) = (number of parts of the compound / molecular weight of the compound (g / mol)) x (number of aromatic rings bonded to heteroatoms in one molecule of the compound) x 1000

[0081] (Preparation of bonding samples) A 4-inch silicon wafer (diameter 10 cm × thickness 0.47 mm) and a 4-inch glass support member (diameter 10 cm × thickness 0.7 mm) were bonded together using the liquid composition. The thickness of the liquid composition was adjusted to 50 μm during bonding. After bonding, the wafer was irradiated with a black light having a wavelength of 365 nm at an illumination intensity of 100 mW / cm. 2 , irradiation time 50 seconds, cumulative light intensity 5000mJ / cm 2 The adhesive was cured under the above conditions, and then placed on a hot plate heated to 180° C. for 30 minutes to prepare a test piece for evaluating adhesiveness. The liquid composition was applied to the entire surface of the bonding surface.

[0082] (Evaluation of laser peelability) A UV laser with a wavelength of 355 nm was irradiated onto a perfect circular area with a diameter of 110 mm fixed at the center of the obtained 4-inch test piece so as to scan the entire surface of the test piece from the glass support member side.

[0083] A razor blade was applied to the circumference of the test piece after the laser irradiation to remove any protruding parts from the circumference. The test piece was placed on a porous chuck-type suction table with the silicon wafer facing down and fixed in place, and three suction cups with a diameter of 30 mm were attached to the glass support member of the test piece from above. A load measurement module was attached to the suction cups, and the glass support member was pulled up vertically to measure the load applied to peel the glass support member. As a parameter for evaluating peelability, the laser output (W) required to enable glass peeling up to a load of 10 N was measured and shown in Tables 1-1 and 1-2. The smaller the value, the easier it is to peel.

[0084] [Table 1-1] The unit of usage is parts by mass.

[0085] [Table 1-2] The unit of usage is parts by mass. × indicates that the temporary fixative was cracked.

[0086] From the results of Tables 1-1 and 1-2, it was found that the temporary fixing composition of the present invention has a low laser output that requires peeling and has high peelability, which enables peeling in a state where heat generation is suppressed.

[0087] On the other hand, in Comparative Example 1, in which the equivalent weight of the aromatic ring bonded to the heteroatom is below the lower limit of the range of the present invention, the laser output required for peeling is high, and peelability is poor. In Comparative Example 2, the temporary fixing agent cracked when the test piece was heat-treated, and evaluation was not possible.

Claims

1. A temporary fixing composition comprising the following (A) to (C): (A) a polymerizable component comprising a (meth)acrylate containing an aromatic ring bonded to a heteroatom (B) Photoradical polymerization initiator (C) UV absorber having a polymerizable functional group the equivalent amount of the aromatic ring bonded to a heteroatom contained in 1 g of the temporary fixing composition is 0.50 mmol or more and 3 mmol or less; A temporary fixing composition comprising 0.5 to 15 parts by mass of the component (C) relative to a total of 100 parts by mass of the component (A).

2. The component (A) is 9,9-bis[4-(2-hydroxyphenyl)- 1 ~C 20 alkoxy)phenyl]fluorene di(meth)acrylate, C 1 ~C 20 Alkoxylated bisphenol A di(meth)acrylate, 1,3-bis(2-(meth)acryloyloxy C 1 ~C 20 2. The temporary fixing composition according to claim 1, comprising at least one selected from the group consisting of 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, 2,2-bis(4-(meth)acryloxydiethoxyphenyl)propane, and structural isomers thereof.

3. The temporary fixing composition according to claim 1 , wherein the component (A) contains one or more selected from the group consisting of nonylphenoxy polyethylene glycol (meth)acrylate, phenoxyethyl (meth)acrylate, or structural isomers thereof.

4. The temporary fixing composition according to claim 1 or 2, wherein the component (B) is one or more selected from bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide and 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]ethanone 1-(O-acetyloxime).

5. The temporary fixing composition according to claim 1 or 2, wherein the component (C) has one or more skeletons selected from the group consisting of a benzophenone skeleton, a triazole skeleton, a hydroxyphenyltriazine skeleton, and a phenol skeleton, and has a polymerizable functional group.

6. The temporary fixing composition according to claim 1 or 2, comprising 0.01 to 5 parts by mass of the component (B) relative to a total of 100 parts by mass of the component (A).

7. A temporary fixing adhesive comprising the temporary fixing composition according to claim 1 or 2.

8. A method for producing a thin wafer using the temporary fixing adhesive according to claim 7, a step of bonding a base material of a thin wafer and an optically transparent support member via the temporary fixing adhesive; a step of photocuring the temporary fixing adhesive from the support member side to form an adhesive layer and bonding the base material and the support member; processing the substrate to form a thin wafer; A step of irradiating the support member with light having a wavelength of 350 nm to 385 nm to decompose the adhesive layer and peel off the thin wafer from the support member. The method includes:

9. A composition comprising the following (A) to (C): (A) a polymerizable component comprising a (meth)acrylate containing an aromatic ring bonded to a heteroatom (B) Polymerization initiator (C) UV absorber having a polymerizable functional group the equivalent of the aromatic ring bonded to a heteroatom contained in 1 g of the composition is 0.50 mmol or more and 3 mmol or less; A composition comprising 0.5 to 15 parts by mass of the component (C) relative to a total of 100 parts by mass of the component (A).

Citation Information

Patent Citations

  • Tape for grinding rear of wafer and usage thereof

    JP1994177094A

  • Composition for adhesive layer, layered product, and producing and processing method for the layered product

    JP2023008789A

  • Benzotriazole based (METH)acrylate copolymer and adhesive composition comprising same

    KR1020150024708A

  • Composition

    WO2021235406A1

  • Composition

    WO2022230874A1